Autores - Rivas, Ramón D. (Kóot, 2015)
José Heriberto Erquicia Cruz Francisco Roberto Gallardo Mejía Martha Marielba Herrera Reina Carmen Molina Tamacas Carlos Payés Héctor Samour Dennis Sevillano Payés